The Influence of Corporate Governance, Goodwill, and Asset Effectiveness on Company Value with Earnings Quality as an Intervening Variable in Non-Manufacturing Companies Registered on ISSI in 2019-2023 - Faizah, Isnaini Nurul; Putri Pertiwi, Imanda Firmantyas (Social Science Studies, 2025)
Research Aims : This study aims to explore the influence of corporate governance, goodwill, and asset effectiveness on firm value with earnings quality as a mediator in the context of public companies in Indonesia. Design/methodology/approach : The method used in the study is a quantitative approach with secondary data collection through the website www.idx.co.id. This study uses a population of 583 companies on the Indonesian Sharia Stock Index (ISSI) and regression analysis to test the hypothesis. Data processing uses the Eviews 10 software testing tool. Sampling in this study uses a purposive sampling technique, so that a sample of 48 companies is obtained in a 5-year period. Research Findings : The results of this study indicate that corporate governance has a negative and insignificant impact on firm value. Goodwill can have a significant negative effect on firm value. Asset effectiveness can have a significant positive effect on firm value. Earnings quality has a negative and insignificant impact on firm value. Corporate governance has a negative and insignificant impact on earnings quality. Goodwill has a positive and insignificant impact on earnings quality. Asset effectiveness has a significant positive effect on earnings quality. Earnings quality cannot mediate the effect of corporate governance on firm value. Earnings quality cannot mediate the effect of goodwill on firm value. Earnings quality cannot mediate the effect of asset effectiveness on firm value. Theoritical Contribution/Originality : With this research, it provides insight into the relationship between corporate governance, goodwill, asset effectiveness, and earnings quality to the company's value which is expected to be useful for researchers usually to identify emerging issues for community service, community benefits, and self-discovery. This finding also enlightens corporate stakeholders to implement effective governance to increase company value while also providing various valuable information and knowledge.